Sub-Cellular Damage of Hepatocytes Caused by Different Doses of Diclofenac Sodium in Rabbit - Talat Yasmeen; Farzana Yasmin (Journal of Basic & Applied Sciences, 2016)
Diclofenac sodium is a potent analgesic and anti-inflammatory drug that is extensively prescribed in treatment of rheumatoid arthritis, postoperative pain, and chronic pain associated with cancer. The present study was designed to elucidate the qualitative and quantitative changes in rough endoplasmic reticulum of hepatocytes after recommended single, double and triple therapeutic dose of Diclofenac sodium in rabbits. The aim of study is to minimize the indiscriminate use of this drug in community and among physicians. Experimental study was carried at Dow University of Health Sciences (DUHS) and Sindh Institute of Urology and Transplantation (SIUT) from March 2009 to June 2010. Eighty eight healthy animals of three months age and 900 1000 gm body weight were isolated from the animal house of DUHS. These animals were divided into four groups categorized into Group A, Group B, Group C, Group D, each containing twenty two animals. Diclofenac sodium were administered intraperitoneally with the daily doses of 2, 4, and 6 mg/kg body weight for 14 consecutive days in Groups B, C and D while the control group (Group A) received normal saline. Animals were sacrificed on day fifteen and livers were removed and fixed in 4% gluterldehyde. They were processed for electron microscopy and examined under transmission electron microscope. Data was collected and subjected for statistical analysis a ‘P’ value less than 0.05 was taken as significant. It was observed that Diclofenac sodium produces significant changes in hepatocytes. There was de-granulation and swelling of the cisternae of Rough Endoplasmic Reticulum (RER) when the dose is doubled and these changes were highly significant when the dose is increased to three times the therapeutic.